Controlling network topology and mechanical properties of co‐assembling peptide hydrogels. Issue 6 (June 2014) - Boothroyd, Stephen; Saiani, Alberto; Miller, Aline F.
ABSTRACT Oligopeptides are well‐known to self‐assemble into a wide array of nanostructures including β‐sheet‐rich fibers that when present above a critical concentration become entangled and form self‐supporting hydrogels. The length, quantity, and interactions between fibers influence the mechanical properties of the hydrogel formed and this is typically achieved by varying the peptide concentration, pH, ionic strength, or the addition of a second species or chemical cross‐linking agent. Here, we outline an alternative, facile route to control the mechanical properties of the self‐assembling octa‐peptide, FEFEFKFK (FEKII); simply doping with controlled quantities of its double length peptide, FEFEFKFK‐GG‐FKFKFEFE (FEKII18). The structure and properties of a series of samples were studied here (0–100 M% of FEKII18) using Fourier transform infrared, small angle X‐ray scattering, transmission electron microscopy, and oscillatory rheology. All samples were found to contain elongated, flexible fibers and all mixed samples contained Y‐shaped branch points and parallel fibers which is attributed to the longer peptide self‐assembling within two fibers, thus creating a cross‐link in the network structure. Such behavior was reflected in an increase in the elasticity of the mixed samples with increasing quantity of double peptide. Interestingly the elastic modulus increased up to 30 times the pure FEKII value simply by adding 28 M% of FEKII18. These observations provide an easy, off‐the‐shelf method for an end‐user to control the cross‐linked network structure of the peptide hydrogel, and consequently strength of the hydrogel simply by physically mixing pre‐determined quantities of two similar peptide molecules. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 669–680, 2014.